Assessing the sustainability of Saving and Micro-Credit Programme (SMCP), Eritrea - Tesfamariam, Berhane Ghebreslasie (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2004.